Integrity and Global Leadership - Morrison, Allen (Journal of business ethics, 2001)
This paper addresses the role of integrity in global leadership. It reviews the philosophy of ethics and suggests that both contractarianism and pluralism are particularly helpful in understanding ethics from a global leadership perspective. It also reviews the challenges to integrity that come through interactions that are both external and internal to the company. Finally, the paper provides helpful suggestions on how global leaders can define appropriate ethical standards for themselves and their organizations.